Relationship between Malaysian ESL learners' motivation, engagement, learning styles, autonomy readiness, and teachers' instructional behaviors and language learning autonomy - Foroutan, Maryam (2013)
The purpose of this research was to investigate if significant relationships existed among language learning autonomy readiness, perceived teacher’s instructional behavior, language learning motivation, engagement, learning styles (independent variables) and language learning autonomy (dependent variable). Three hundred and sixty lower form-6 students were randomly selected from secondary schools in Selangor, Malaysia where they were asked to fill in the corresponding questionnaires. Descriptive statistics and Pearson product-moment correlation procedures were applied to answer the questions concerning the extent of each variable as well as the relationship between students’ language learning autonomy extent and each independent variable in the study. In addition, stepwise regression procedures were applied to explore the highest to the least contribution of the independent variables toward the dependent variable. Along with quantitative procedures, qualitative data through interview and observation assisted the researcher to support the quantitative findings. The findings of descriptive data through both quantitative and qualitative data disclosed that the participants possessed moderately low autonomy extent, but moderately high autonomy readiness. Perceived teachers’ instructional behavior data indicated moderately autonomy-supportive behavior. However, observation demonstrated teachers’ moderately controlling behavior. The data collected from engagement and motivation surveys each showed moderate and high levels respectively. The relationship between autonomy extent and each independent variable of the study showed considerable findings. The relationship between autonomy extent and autonomy readiness revealed a low, but positive relationship. The relationship between autonomy extent with perceived teacher’s instructional behavior and engagement both showed moderate and positive direction.Unexpectedly, the findings revealed that autonomy extent and overall motivation had no significant relationship. Examining the relationship between each motivation categories and autonomy, the results showed that both intrinsic and identified regulation had low, but positive relationship, external regulation had no relationship, and introjected regulation had negative but negligible relationship. Apart from that, the relationship between autonomy extent and the total score of learning styles showed low, but positive direction. Findings also revealed that all learning styles, but individual and group, and language learning autonomy extent had positive relationships. The regression analysis displayed that the highest to the least contribution to autonomy extent (dependent variable) belonged to perceived teachers’ instructional behavior, course engagement, autonomy readiness and learning styles. The results of this study suggest the importance of promoting autonomy among secondary school students in Malaysia. Despite the fact that Malaysian students possess low autonomy extent and are mostly auditory and visual learners; culturally and individually these students have the essential readiness to accept responsibility for their own learning. Moreover, the English teacher has the pivotal role to play in providing the conditions for promoting autonomous learning in order to enhance motivation and engagement in students’ language learning.